(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
We obtain equivalent assertions among the integrability conditions of generalized almost contact manifolds, the condition of compatibility of source and target maps of symplectic groupoids with symplectic form and generalized contact maps.